2007
DOI: 10.1007/s10540-007-9041-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Diseases: Therapeutic Approaches

Abstract: Therapy of mitochondrial encephalomyopathies (defined restrictively as defects of the mitochondrial respiratory chain) is woefully inadequate, despite great progress in our understanding of the molecular bases of these disorders. In this review, we consider sequentially several different therapeutic approaches. Palliative therapy is dictated by good medical practice and includes anticonvulsant medication, control of endocrine dysfunction, and surgical procedures. Removal of noxious metabolites is centered on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
93
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 64 publications
0
93
0
3
Order By: Relevance
“…6 The main causes of mitochondrial dysfunction are mutations of mitochondrial DNA 3 and interruption of the homeostatic loop between mitochondria and the reactive oxygen species generated by mitochondrial respiratory chain activity. 7 Supporting the strategy that mitochondrial dysfunction may be protected/reversed by drugs capable of regulating and improving mitochondrial processes, 8 we suggested that mildronate, a drug of aza-butyrobetaine class, may target mitochondria. This suggestion is based on previous data showing that mildronate is capable of protecting mitochondrial membranes from damage by free fatty acids (FFAs), 9 as well as from AZT-induced morphological changes and activation of nuclear factor kBp65 in mice cardiac tissue.…”
Section: Introductionmentioning
confidence: 78%
“…6 The main causes of mitochondrial dysfunction are mutations of mitochondrial DNA 3 and interruption of the homeostatic loop between mitochondria and the reactive oxygen species generated by mitochondrial respiratory chain activity. 7 Supporting the strategy that mitochondrial dysfunction may be protected/reversed by drugs capable of regulating and improving mitochondrial processes, 8 we suggested that mildronate, a drug of aza-butyrobetaine class, may target mitochondria. This suggestion is based on previous data showing that mildronate is capable of protecting mitochondrial membranes from damage by free fatty acids (FFAs), 9 as well as from AZT-induced morphological changes and activation of nuclear factor kBp65 in mice cardiac tissue.…”
Section: Introductionmentioning
confidence: 78%
“…We used a cocktail of vitamins and co-factors based on established treatments of mitochondrial disorders associated with lactic acidosis [9,10]. Thiamine, vitamin B1, is a co-factor in multiple steps in amino acid and carbohydrate metabolism, including the conversion of pyruvate to acetylCoA.…”
Section: Discussionmentioning
confidence: 99%
“…Free-radical mediated injury may occur as a consequence of mitochondrial dysfunction [10]. To mitigate this, we treated with the free-radical scavenger NAC, using dosing standards for acetaminophen-associated liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…This often involves multiple disciplines: both physicians (neurologists, cardiologists, diabetologists, and ophthalmologists) and specialist nurses, physiotherapists, and speech therapists, depending on the clinical phenotype. 4 Although huge advances have been made over the last decade in relation to the function and structure of mitochondria and subsequently the pathogenic mechanisms underlying mitochondrial disease, there is currently no definitive pharmacological treatment for patients with mitochondrial dysfunction, 5 except for patients with primary deficiency of coenzyme Q10. Nonpharmacological treatments are increasingly being investigated, including ketogenic diet, exercise, and gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Nonpharmacological treatments are increasingly being investigated, including ketogenic diet, exercise, and gene therapy. 4 Management is aimed primarily at minimizing disability, preventing complications, and providing prognostic information and genetic counseling based on current best practice. 6 -9 …”
Section: Introductionmentioning
confidence: 99%